PHENOTYPIC MANIFESTATION OF ANTHOCYANIN COLOR - Ya.B.Tursunov; Sh.L.Yuldasheva (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article analyzes the genetic and environmental factors that influence the phenotypic expression of anthocyanin pigments. The mechanisms involved in the biosynthesis, transcriptional control, and phenotypic expression of anthocyanins in plants are reviewed based on scientific sources.